Penerapan Metode Waterfall Dalam Rancang Bangun Sistem Informasi Inventory Perlengkapan Sales PT NF Indonesia Berbasis Web - Prasetyo, Feri; Hizatullah, Nizar (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2022)
Computers are equipment created to help facilitate human work, which makes work more organized. Industry and warehousing really need an information system that supports and provides accuracy in inventory and data management. Based on observations in the promotional warehouse, this promotional warehouse requires the development of computerization in processing and managing the inventory of its goods. Which is currently in the data storage recap receipt of incoming goods, cutting inventory of outgoing goods and making travel documents are still manual with ms.excel format. so that it is still possible to have inaccuracies in the data with the existing physical goods, and difficulties in making the delivery document because it is still manual. The design of this program is the best solution to solve the problems that exist in managing inventory in this warehouse. Development by changing process tools from excel to web-based can support the activities and management of goods data as well as the allocation of goods based on the delivery destination where the data will be more accurate, efficient and effective in the process Keywords : Sales, Inventory, Web